CREATION OF A NEW AGING IN PLACE MEASURE. (11th November 2018) - Weil, J
Abstract: Aging in place and other "place" terms (such as stuck in place, aging in the right place, aging out of place, and age-friendliness) are often discussed in the gerontological literature. Yet, a validated measure that incorporates this new diversity of place definitions and person-environment fit does not exist. The creation of a more inclusive and comprehensive measure is crucial as the aging-in-place concept grows and expands to include the broader continuum of care. This study reports findings from steps in the process of developing a quantitative measure. Namely, we report findings from the first 4 steps of gerontologist Neal Kraus' a 9-step Measurement Development model that we used to create a measure of aging in place for older adults. This process consisted of several steps and sources from: in-depth and focus group data, literature review, and selecting and testing items from existing comparable measures. Specifically, data analysis of 84 hours of in-depth interview narrative, from May 2017 to present, is discussed. Data arose from a combination of focus group and interview narrative. Initially, these data illustrate how the original conceptual domains were created. Then, we present examples of how the conceptual domain pool was further expanded through a systematic literature review and by review and assessment of comparable measures to develop our new aging in place questionnaire. Both this measure development process and findings are applicable to the creation of measures about other gerontological topics.